2016
DOI: 10.1155/2016/3745298
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Perceptions, and Practice of Nurses on Surveillance of Adverse Events following Childhood Immunization in Nairobi, Kenya

Abstract: Background. Although vaccines currently approved for routine childhood immunization are safe and effective, frequent adverse events following immunization often cause illnesses and sometimes loss of public trust in immunization programs. Nurses are essential in this surveillance system. Objective. To determine nurses' knowledge, perception, and practice towards surveillance of postimmunization adverse events within Nairobi County health centers, Kenya. Methods. This is a cross-sectional survey involving nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 17 publications
4
32
0
Order By: Relevance
“…It was also consistent with a more recent study in Zaria, Northwestern Nigeria, which showed 58.9% of the respondents as having good knowledge on AEFI [22]. However, our finding was in contrast to that of Masika et al [16] in Kenya where less than 30% of the respondents had good knowledge on AEFI. Though the overall AEFI knowledge status of the respondents in the present study was good, knowledge gaps exist in some specific areas.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was also consistent with a more recent study in Zaria, Northwestern Nigeria, which showed 58.9% of the respondents as having good knowledge on AEFI [22]. However, our finding was in contrast to that of Masika et al [16] in Kenya where less than 30% of the respondents had good knowledge on AEFI. Though the overall AEFI knowledge status of the respondents in the present study was good, knowledge gaps exist in some specific areas.…”
Section: Discussionsupporting
confidence: 92%
“…This is comparable to a study in Srilanka where 92% of nurses showed good knowledge on how to use adrenaline in the management of anaphylaxis [27]. However, the study result is in contrast with findings from an earlier study in Kenya, where less than 40% of the nurses knew how to manage post immunization anaphylaxis [16]. Generally, the incidence of severe adverse events such as anaphylaxis resulting from immunization is rare [28].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…They also add the need to develop educational strategies on the subject. 31 The constant changes that occur in immunobiological agents also reveal the need for PE, as highlighted by the participants of this study.…”
Section: Vaccination In Everyday Life and Permanent Educationmentioning
confidence: 79%
“…The main finding in these papers was that PEP was underused, and it was speculated that this was partly due to the low level of PEP-related knowledge. Forty-eight questions were about different types of vaccines; 23 on hepatitis B [39][40][41][42][43], eight on human papilloma virus [44][45][46], three on influenza [47,48] viruses, and 14 questions on adverse events following immunization [49]. Questions were about overall awareness of different types of vaccines, and the effectiveness, what comprised a dose/full course, how long the vaccines offered protection, and about the safety of vaccination, adverse reactions after immunization, and medication used to prevent/relieve vaccinationrelated immune reaction.…”
Section: Disease Focusmentioning
confidence: 99%